Gan Transistor in Space Equipments: From Selection to Applications - Fayt Philippe; Fossion Marc; Maynadier Paul; Notarianni Michaël (E3S Web of Conferences, 2017)
Two years ago, at ESPC-2014 results of ESA activity on GaN transistor survey has been presented. The main outcome was the existence of an unknown phenomena in silicon MOSFET: the dynamic Rdson. Today we are the time of studying introduction of this technology into products. At least two suppliers (EPC- co & GaN Systems) are proposing stabilized GaN transistors components which are worth spending some time to try to implement in next generation product prototypes. Space applications aren’t very different from terrestrial ones when we speak about benefits of using GaN technology into dc-dc converters: lower losses & more compact designs thanks to higher switching frequencies. Next to reliability analyses proposed by the component vendors to be able to address the automotive markets, there is of course quite a list “space” specific questions that need also to be answered to raise the confidence that GaN will one day be put is orbit: hermetic packaging & assembly on PCBs, radiation harness, reliability impact of radiations, cooling in the absence of air flow, thermal cycling, drivers, deratings to apply… In this article we presents some prototyping results & shares some feedback & concerns about the introduction of GaN into space qualified dc-dc products.